Feel Your Reach: An EEG-Based Framework to Continuously Detect Goal-Directed Movements and Error Processing to Gate Kinesthetic Feedback Informed Artificial Arm Control - Müller-Putz, Gernot R.; Kobler, Reinmar J.; Pereira, Joana; Lopes-Dias, Catarina; Hehenberger, Lea; Mondini, Valeria; Martínez-Cagigal, Víctor; Srisrisawang, Nitikorn; Pulferer, Hannah; Batistić, Luka; Sburlea, Andreea I. (Frontiers in Human Neuroscience, 2022)
Establishing the basic knowledge, methodology and technology for a framework for the continuous decoding of hand/arm movement intention was the aim of the ERC-funded project ‘Feel Your Reach’. In this work we review the studies and methods we performed and implemented in the last six years, which build the basis for enabling severely paralyzed people to non-invasively control a robotic arm in real-time from electroencephalogram (EEG). In detail, we investigated goal-directed movement detection, decoding of executed and attempted movement trajectories, grasping correlates, error processing and kinesthetic feedback. Although we have tested some of our approaches already with the target populations, we still need to transfer the ‘Feel Your Reach’ framework to people with cervical spinal cord injury and evaluate the decoders’ performance while participants attempt to perform upper-limb movements. While on the one hand, we made major progress towards this ambitious goal, we also critically discuss current limitations.